2014
DOI: 10.1002/hyp.10369
|View full text |Cite
|
Sign up to set email alerts
|

Remnant riparian vegetation, sediment and nutrient loads, and river rehabilitation in subtropical Australia

Abstract: A decline in the ecosystem health of Australia's Moreton Bay, a Ramsar wetland of international significance, has been attributed to sediments and nutrients derived from catchment sources. To address this decline the regional management plan has set the target of reducing the loads by 50%. Reforestation of the channel network has been proposed as the means to achieve this reduction, but the extent of revegetation required is uncertain. Here we test the hypothesis that sediment and nutrient loads from catchment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…This role may be even more important in event-driven systems where high rainfall and runoff generate high stream power and strong erosive forces on the channel network. Intact riparian vegetation can significantly reduce the export of this material from the terrestrial to aquatic environment [15,16]. Retaining these sediment and nutrient resources also enhances the ability of catchments to deliver valuable ecosystem services by, for example, supporting agricultural production with reduced requirement for artificial fertilizer inputs [17].…”
Section: Water Quality and The Ecology Of Riversmentioning
confidence: 99%
See 3 more Smart Citations
“…This role may be even more important in event-driven systems where high rainfall and runoff generate high stream power and strong erosive forces on the channel network. Intact riparian vegetation can significantly reduce the export of this material from the terrestrial to aquatic environment [15,16]. Retaining these sediment and nutrient resources also enhances the ability of catchments to deliver valuable ecosystem services by, for example, supporting agricultural production with reduced requirement for artificial fertilizer inputs [17].…”
Section: Water Quality and The Ecology Of Riversmentioning
confidence: 99%
“…This has led to the determination of the effect of remnant riparian vegetation on sediment and nutrient loads delivered to waterways in the region [16]. Using event-based water quality data, Olley et al found that the sediment yield per unit area from cleared catchments is between 50 and 200 times that of fully vegetated catchments, with a best estimate of 100 times [16]. For total phosphorus it is between 25 and 60 times, with a best estimate of 40 times, and for total nitrogen between 1.6 and 4.1 times.…”
Section: Restoration Approaches: Addressing Ecosystem Health Decline mentioning
confidence: 99%
See 2 more Smart Citations
“…Deforestation and farming increase run-off of nutrients and sediment that can flow out to the ocean 4 . In the ocean, sediment and nutrient pollutants can decrease water clarity and shade or smother habitats, reducing diversity of benthic organisms 5 , habitat complexity and fish diversity 6, 7 .…”
Section: Introductionmentioning
confidence: 99%